Bromatological composition of vetch (Vicia sativa L) silage associated with barley (Hordeum vulgare L) and urea - Contreras Paco, José Luis (2020)
The present study aimed to determine the bromatological composition of the vetch silage associated with barley in five proportions and two levels of urea. A completely randomized design with three repetitions in a factorial scheme of 5 x 2 (proportions, urea) was used. The ratios of vetch and barley were: 0: 100, 25:75, 50:50, 75:25 and 100:0, respectively. Urea was added in 0 and 1% levels on a dry matter basis. Micro silos of PVC tubes 10 cm (diameter) x 60 cm (height) were used for 121 days. Samples were taken from the silos to determine dry matter (DM), crude protein (CP), neutral detergent fibre (NDF), acid detergent fibre (ADF), hemicellulose, mineral matter (MM) and pH. The vetch:barley 50:50, 75:25 and 100:0 without urea had higher DM content than the ammonified silages (p<0.05). The CP increased linearly in the silages with and without urea, especially the vetch/barley ammoniates: 25:75 and 50:50. The NDF of the ammoniated vetch/barley ratios presented a negative linear effect (52.58 to 45.30% of NDF), as did hemicellulose (21.92 to 9.51%). The FDA also decreased vetch/barley silages without and with urea with the ratio of 75:25 (35.92 to 31.23% of FDA). It is confirmed that the urea ammonification improved the nutritional value of the vetch-barley association.